A novel method developed for estimating mineralization efficiencies and its application in PC and PEC degradations of large molecule biological compounds with unknown chemical formula. (15th May 2016) - Li, Guiying; Liu, Xiaolu; An, Taicheng; Wong, Po Keung; Zhao, Huijun
Abstract: A new method to estimate the photocatalytic (PC) and photoelectrocatalytic (PEC) mineralization efficiencies of large molecule biological compounds with unknown chemical formula in water was firstly developed and experimentally validated. The method employed chemical oxidation under the standard dichromate chemical oxygen demand (COD) conditions to obtain Q COD values of model compounds with unknown chemical formula. The measured Q COD values were used as the reference to replace Q COD values of model compounds for calculation of the mineralization efficiencies (in %) by assuming the obtained Q COD values are the measure of the theoretical charge required for the complete mineralization of organic pollutants. Total organic carbon (TOC) was also employed as a reference to confirm the mineralization capacity of dichromate chemical oxidation. The developed method was applied to determine the degradation extent of model compounds, such as bovine serum albumin (BSA), lecithin and bacterial DNA, by PC and PEC. Incomplete PC mineralization of all large molecule biological compounds was observed, especially for BSA. But the introduction of electrochemical technique into a PC oxidation process could profoundly improve the mineralization efficiencies of model compounds. PEC mineralization efficiencies of bacterial DNA was the highest, while that of lecithin was the lowest. Overall, PEC degradation method was found to be much effective than PC method for all large molecule biological compounds investigated, with PEC/PC mineralization ratios followed an order of BSA > lecithin > DNA. Graphical abstract: Highlights: A new method was developed to estimate the mineralization of large compounds. The method was experimentally validated using large molecule biological compounds. Estimating PC and PEC mineralization of compounds with unknown chemical formula.